2020
DOI: 10.3390/agronomy10030382
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Carbon Storage in Coffee Agroecosystems: The Case of the Central Region of the State of Veracruz in Mexico

Abstract: This study quantifies the aboveground C storage of coffee agroecosystems (AESs) present in the Xalapa–Coatepec region of the state of Veracruz, one of the most important coffee producing regions in Mexico. We identified and determined the spatial distribution of five different types of coffee AESs. Then, through the point-centered quarter method, we measured canopy coverage, total height, diameter at breast height and density of tree species at 160 randomly selected sampling sites. Using allometric models, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
5
0
1
Order By: Relevance
“…Higher aboveground biomass C stock potential was found for plantations in the tropics, such as palm oil, cocoa, orange, and rubber, with values of 45, 65, 76, and 214 Mg C ha −1 , respectively (Kongsager et al 2013), due to the larger tree architecture and the climate associated with higher NPP. Furthermore, a mean value of 55.12 Mg C ha −1 was reported for coffee agroecosystems in Mexico (Ortiz-Ceballos et al 2020). At the global level, Zomer et al (2016) reported 28 Mg C ha −1 in 2000 and 29 Mg C ha −1 in 2010, and in particular, 9.3 and 9.4 Mg C ha −1 in Europe for agroforestry and tree cover on agricultural land, values in line with those published in this study.…”
Section: Biomass Carbon Stock Upscaling To the Levelsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher aboveground biomass C stock potential was found for plantations in the tropics, such as palm oil, cocoa, orange, and rubber, with values of 45, 65, 76, and 214 Mg C ha −1 , respectively (Kongsager et al 2013), due to the larger tree architecture and the climate associated with higher NPP. Furthermore, a mean value of 55.12 Mg C ha −1 was reported for coffee agroecosystems in Mexico (Ortiz-Ceballos et al 2020). At the global level, Zomer et al (2016) reported 28 Mg C ha −1 in 2000 and 29 Mg C ha −1 in 2010, and in particular, 9.3 and 9.4 Mg C ha −1 in Europe for agroforestry and tree cover on agricultural land, values in line with those published in this study.…”
Section: Biomass Carbon Stock Upscaling To the Levelsupporting
confidence: 89%
“…Moreover, Montanaro et al (2017) estimated the carbon budget in a Mediterranean peach orchard under different management practices in Italy and estimated lifetime C sequestration in the standing biomass of 14-year-old peach trees. A number of studies have estimated woody biomass on agricultural land in non-Mediterranean regions (Kumar et al 2010;Kuyah et al 2012aKuyah et al , 2012bKongsager et al 2013;Kuyah et al 2016;Ortiz-Ceballos et al 2020;Asigbaase et al 2021) and globally (Zomer et al 2016;Spawn et al 2020). There are fewer studies on changes in land use (LUC) and associated carbon sequestration potential (Padilla et al 2010;Huffman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…with Macadamia sp., I. vera, Musa x paradisiaca L. (34.0, 29.0, and 27.0 t ha −1 ) [26], and Coffea sp. with Acacia pennatula (38.47 t ha −1 ) [66], but are lower than Coffea sp. systems with Inga sp.…”
Section: Estimation Of Carbon Contentmentioning
confidence: 85%
“…Means of the carbon stocks in aerial biomass, soil, and total C + SD (t ha -1 ) simulated with the CO2Fix model over a period of fifty years shade trees -coffee (C. arabica L.) -banana in the valley evaluated in the Sociedad Catuai Amarillo S. de SS, Chocaman, Veracruz, Mexico under the different scenarios in the three-time horizons (near, medium and distant future). 2021. inferiores a los datos reportados por Ortiz-Ceballos et al (2020), quienes registraron 55,12 t ha -1 en sistemas agroforestales con café en la región Xalapa-Coatepec, Veracruz, México. Esto se pudo deber a la densidad de árboles e intensidad de manejo que se le dio a los diseños agroforestales evaluados (Salgado-Mora et al, 2018).…”
Section: Discussionunclassified